Immunotherapy Management in Special Cancer Patient Populations. Issue 5 (May 2021) - Ramnaraign, Brian H.; Chatzkel, Jonathan A.; Al-Mansour, Zeina A.; Rogers, Sherise; Jones, Dennie; DeRemer, David; George, Thomas J.
Abstract : Patients with autoimmune disorders, multiple comorbidities, poor performance status, advanced age, and infection with SARS-CoV-2 (COVID-19) each represent unique subgroups of patients with cancer to whom little is known of the effects, benefits, and complications of checkpoint inhibitor (CPI) therapy. Although prospective trials are lacking in these populations, retrospective data and cohort series suggest that these patients can safely receive and benefit from CPI therapy. Here, we review the relevant data available and offer clinical recommendations in managing these complex patients with CPI therapy, where otherwise indicated.